Lifestyles of Spanish elders from supervened SARS-CoV-2 variant onwards: A correlational research on life satisfaction and social-relational praxes - Díaz-García, Orlanda; Herranz Aguayo, Inmaculada; Fernández de Castro, Patricia; Ramos, José Luis Gómez (Frontiers in Psychology, 2022)
Objective This study aimed to analyze the influence and measurement of the relationship and interaction between the elderly lifestyles after the appearance of the SARS-CoV-2 variant and the factors analyzed comprised life satisfaction levels, social relationships, and daily-life activities. Methods The study population was ≥ 65 in Castile-La Mancha (N = 390,221). The research design was quantitative and arose from primary data collected via an ad hoc survey carried out through the Computer Assisted Telephone Interview system by randomly stratified sampling. The sample size was made up of 1,065 cases, and the participants were selected through a random sampling stratified by gender quotas (55.40% women; 44.60% men), age (x¯ = 76.56), province, and habitat size. Results The results obtained revealed two main lifestyles, from which a notable behavioral change in personal relationships led to infer toward alternative lifestyles. Conclusion Notwithstanding the variation in lifestyles of the elderly after the pandemic, certain relationships remained unaltered. Thus, from the analyzed variables, relatives and friends relationships were scarcely influenced by the supervened incident.